Case Report: The many faces of bullous pemphigoid - Rechtien, Laura; Sollfrank, Lukas; Foerster, Yannick; Berking, Carola; Sticherling, Michael (Frontiers in Immunology, 2023)
The pemphigoid group comprises a number of bullous skin diseases with autoantibodies against different constituents of the basement membrane zone that result in subepidermal detachment and clinically characteristic tense blisters, erosions, urticarial erythema, and itching. Apart from the most frequent type of bullous pemphigoid with antibodies against BP180, which is found predominantly in elderly patients, the disease may present at other ages and different pathogenic conditions. Here, four cases are presented of young age (3 months and 25, 34, and 46 years) and in association with vaccination, pregnancy, or metastatic cancer. Though anti-BP180 was found in all cases, a different pathogenic background may be found in any of them, resulting in characteristic clinical manifestation, yet demanding specifically adapted therapeutic approaches.